Urban Mobility and Social Relationships: A Case Study of Passenger Vans in Bangkok Metropolitan Region - Sirikasemchai, Napaphat (Journal of Social Sciences, Chiang Mai University, 2023)
The research aims to answer how the passenger vans participate in city life and the different meanings between traveling by the passenger vans and other transportation in the Bangkok Metropolitan Region. To show urban activities, social relationships, and the daily experiences of passengers that the passenger vans get involved as moving agents as well as the relationship between the suburbs and the city where the passenger vans are part of the construction through the participant observation method and interview with 5 passengers who frequently use the passenger vans in the Bangkok Metropolitan Region with relevant anthropological theories.